MODELS FOR BALANCED DEVELOPMENT OF BULGARIAN RURAL REGIONS IN THE CONTEXT OF CAP POST-2020 - R. Beluhova-Uzunova; K. Hristov (Trakia Journal of Sciences)
The development of rural regions and rural disparities are the main issues in the European Union regional policy. The topic continues to be an object of serious discussion among policymakers and scientist. Agriculture plays an important role in rural areas and contributes to generating employment and income. In the past decades, the CAP is reforming and changing to address the challenges in the EU rural regions. The aim of the study is based on the socio-economic analysis of the rural regions in Bulgaria to formulate opportunities for more balanced and sustainable development. The paper observes possibilities and prospects for the rural areas in Bulgaria in the context of the CAP post-2020. The study reveals that depopulation and marginalization of rural regions remain major issues in Bulgaria. Therefore, the implementation of the territorial and local model should dominate in Pillar II for the 2014-2020 programming period. These approaches could stimulate transformations and transition to sustainable regional development. In order to maximize the potential of the Pillar II funding, the national regional policy also should be reviewed.